Arterial Compliance and Continuous-Flow Left Ventricular Assist Device Pump Function. Issue 7 (11th May 2022) - Adji, Audrey; Shehab, Sajad; Jain, Pankaj; Robson, Desiree; Jansz, Paul; Hayward, Christopher S.
Abstract : Durable continuous-flow left ventricular assist devices (cfLVADs) demonstrate superior survival, cardiac functional status, and overall quality of life compared to medical therapy alone in advanced heart failure. Previous studies have not considered the impact arterial compliance may have on pump performance or developed arterial pressure. This study assessed the impact of alterations in arterial compliance, preload, and afterload on continuous-flow pump function and measured hemodynamics using an in-vitro pulsatile mock circulatory loop. Decreased arterial compliance was associated with a significant increase in arterial pressure pulsatility which was not evident in the flow pulsatility, as displayed in pump flow waveforms. There were marked changes in the pump flow waveforms due to the significant alteration in the aortoventricular gradient during diastole according to the changes in compliance. This study demonstrates that changes in systemic blood pressure, afterload, and left ventricular contractility each significantly affects the flow waveform. The association of hypertension with lower aortic compliance results in markedly decreased diastolic flow rates which may be important in contributing to a greater risk of adverse events under cfLVAD support.